Nutritional status, oral hygiene and Angular cheilitis in schoolchildren in Cianjur district, West Java - Partakusuma, Fatimah Boenjamin (Padjadjaran Journal of Dentistry, 2016)
Background: Angular cheilitis is a lesion at the corner of the mouth. Clinically, it is visible as an erythema and ulceration that occasionally extend beyond the vermillion border onto the skin. Anemia in children is an issue of global nutritional problems that need attention. The objectives of the study  was to determine the association between nutritional status, oral hygiene  and angular cheilitis in elementary schoolchildren in District of Cianjur. Methods: This cross sectional study was conducted on 349 schoolchildren in five Subdistrict of Cianjur. Angular cheilitis status was determined based on the criteria set by Ohman (1986). Anhropometric status was determined by CDC BMI-for-age percentile growth chart. Anemia status was determine by the level of hemoglobin concentration using the HemoCue device. Oral hygiene was measured by OHI-S index. Results: The prevalence of angular cheilitis, anemia, wasting and poor oral hygiene were: 62.5%, 12,6%, 20.6%, and 67.3%, respectively. There are no relationships between  anthropometric status, oral hygiene and angular cheilitis. (p> 0.05). However there is a relationship significant relationship beween anemia and angular cheilitis (p <0.05). Logistic regression test showed that anemia is a risk factor on the occurrence of angular cheilitis. Conclusion: Anemia is a factor on the occurrence of angular cheilitis in schoolchildren in Cianjur.